Physics of Earth, Atmosphere, and Geospace from the Standpoint of System Paradigm - Chernogor, L. F. (Видавничий дім «Академперіодика», 2013)
The validation has been provided that the tectonosphere-atmosphere-ionosphere-magnetosphere system (TAIMS) is a complex open dynamic nonlinear system. The basic aspects of the system paradigm have been stated and they are illustrated by many instructive examples. The trigger mechanisms for energy release are demonstrated to be the most important property of the system. It has been shown that highly energetic phenomena in the system give rise to a complex cluster of processes and to the reconstruction in the subsystem coupling. The active experiments in the TAIMS have established the limitation of the linear description of the subsystem response to powerful energy releases, determined the possibility of large-scale and global-scale perturbation onset from local and localized energy releases, as well as revealed and identified the types of waves transferring these disturbances. It has been determined that energetic particle precipitation from the magnetosphere at middle latitudes accompanies the majority of nonsteady processes in the TAIMS.